A call for a national collaborative predator coexistence programme. Issue 4 (13th July 2021) - Carter, Neil H.; Nelson, Peter; Easter, Tara
Abstract: Negative interactions between large terrestrial predators and livestock are a global phenomenon. The resultant conflicts can threaten the livelihoods and cultural traditions of those living closest to predator populations and jeopardize the conservation of predator species. These challenges are pronounced in the United States, where predator conservation is at a defining moment. Focusing on the United States, we advocate for policy initiatives at the national scale to incentivize coexistence on multi‐use public lands. We discuss how such policies can bolster the efforts of local institutions, facilitate bottom‐up collaborations and support science‐based programmes. Modelled after other successful collaborative programmes, our proposed programme could facilitate adoption of effective coexistence strategies across large regions that better match the spatial extent of the interface between predators and livestock. A carefully structured, national coexistence programme could harness the already‐growing support for living alongside healthy predator populations and fundamentally alter how we approach predator management so that political conflicts are avoided. Moreover, elements of the programme can be transferred to other regions around the world where community engagement is essential to sustaining and coexisting with predators. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.